Relationship of the quality of life and depression in the elderly - Eka Suastika; Ni Ketut Sri Diniari; Cokorda Bagus Jaya Lesmana; Luh Nyoman Alit Aryani; Ni Ketut Putri Ariani; Ida Aju Kusuma Wardani (Journal of Clinical and Cultural Psychiatry, 2020)
Background: A good quality of life in the elderly must be maintained because good quality of life is an optimal condition for the elderly to live their daily lives. Depression in the elderly willhave a severe impact on physical, social life where it will reduce the quality of life. This study was conducted to assess the relationship of quality of life with depression in the elderly.Method: This study uses a cross-sectional method, conducted in May-June 2019, using WHOQOL-BREf, GDS, AMT, ADL.Results: A total of 195 elderly participated, average age 67 years, married 94.4 percent, mostly 45.1 percent did not go to school, ADL was found to be normal, there was moderate cognitive impairment as much as 13.3 percent, and depression 80 percent. There was a significant relationship between quality of life and depression (OR: 1.22; 95% IK 1.02-3.97), which means that elderly people with poor quality of life have a higher risk of depression.Conclusion: There is a significant negative correlation between the quality of life with depression, where the elderly with poor quality of life have a 1.22 times greater risk of depression.